2002
DOI: 10.4049/jimmunol.169.6.3242
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Virus-Like Particles Do Not Activate Langerhans Cells: A Possible Immune Escape Mechanism Used by Human Papillomaviruses

Abstract: High-risk human papillomaviruses are linked to several malignancies including cervical cancer. Because human papillomavirus-infected women do not always mount protective antiviral immunity, we explored the interaction of human papillomavirus with Langerhans cells, which would be the first APCs the virus comes into contact with during infection. We determined that dendritic cells, normally targeted by vaccination procedures and Langerhans cells, normally targeted by the natural virus equally internalize human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 48 publications
7
133
0
5
Order By: Relevance
“…In addition, a strong T cell response to L1-VLP was observed when T cells were co-cultured with L1-VLPpulsed autologous DC (average of 15-fold increase over response to DC pulsed with medium, p = 0.008, n = 6). These results are in agreement with previous studies [28]. Since DC-SIGN appeared to be involved in activation of MHC class I antigen and cytokine responses in DC, we examined the effect of DC pulsed with L1-VLP in the The proliferative response of purified T cells after incubation with DC pulsed with L1-VLP in the presence of anti-DC-SIGN antibodies was higher, although not statistically significant, than with DC incubated with VLP alone (approximately 35% increase).…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, a strong T cell response to L1-VLP was observed when T cells were co-cultured with L1-VLPpulsed autologous DC (average of 15-fold increase over response to DC pulsed with medium, p = 0.008, n = 6). These results are in agreement with previous studies [28]. Since DC-SIGN appeared to be involved in activation of MHC class I antigen and cytokine responses in DC, we examined the effect of DC pulsed with L1-VLP in the The proliferative response of purified T cells after incubation with DC pulsed with L1-VLP in the presence of anti-DC-SIGN antibodies was higher, although not statistically significant, than with DC incubated with VLP alone (approximately 35% increase).…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpsupporting
confidence: 94%
“…In addition, a strong T cell response to L1-VLP was observed when T cells were co-cultured with L1-VLPpulsed autologous DC (average of 15-fold increase over response to DC pulsed with medium, p = 0.008, n = 6). These results are in agreement with previous studies [28].…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpsupporting
confidence: 94%
“…It is cleaved via reaction with intracellular esterases into a highly reactive fluorochrome that can be detected by flow cytometry using excitation at 488 nm and the fluorescence 1 detection channel. Thus, fluorescence intensity correlates with the amount of internalized CFSE-labeled VLP [22]. As seen in Fig.…”
Section: Binding and Internalization Of Papillomavirus Vlp By Pdcmentioning
confidence: 71%
“…It was found previously that HPV16 L1 VLP interact with and activate multiple cells of the immune system including monocyte-derived DC (mDC), monocytes and macrophages, providing an experimental explanation for their immunogenicity [19][20][21]. Furthermore, mDC, but not epidermal Langerhans cells, have been shown to present VLP-derived antigenic determinants to primary T cells [19,20,22]. However, it is not known whether pDC share this ability to respond to papillomavirus VLP.…”
Section: Introductionmentioning
confidence: 99%
“…Research on VLP interactions with dendritic cell types have shown that epithelial dendritic cells that are located at the site of natural HPV infection, the Langerhans cells (LC), do not get activated when incubated with VLP and do not initiate epitope-specific immune responses against VLP-derived antigens. 89 This is because LC present HPVderived peptides in the absence of costimulation, thereby becoming immune-suppressive. 90 On the other hand, myeloid dendritic cells are activated by VLP and once activated, they are able to stimulate HPV-specific T cells.…”
Section: Immune Response Modifiersmentioning
confidence: 99%